Analisis Penyebab Anemia berdasarkan Siklus Menstruasi, Pola Makan, dan Asupan Gizi pada Remaja - Catur Wulandari; Dini Setiarsih; Anugrah Linda Mutiarani; Farah Nuriannisa; Alifia Sefty Arruny Wahyudi; Risma Defya Santoso (Media Gizi Kesmas, 2024)
Background: Students as young women are vulnerable to iron deficiency anemia. Anemia in adolescent girls can be caused by factors such as the menstrual cycle, diet, and nutritional intake Objectives: This research aims to analyze the relationship between the menstrual cycle, diet, intake of protein, iron, and vitamin C with the incidence of anemia in adolescent girls Methods: This observational analytical research involves 104 female students as a sample. Anemia is assessed by measuring the respondent's Hb level. Nutritional intake was assessed using the 24-hour recall method. Data analysis was carried out using the Spearman rank test Results: The research results stated that there was a relationship between the menstrual cycle (p-value 0.000); diet (p-value 0.000); protein intake (p-value 0.012); iron intake (p-value 0.001); Vitamin C intake (p-value 0.002) with the incidence of anemia in adolescent girls. Conclusion: The existence of this relationship means that the menstrual cycle, eating patterns, and nutritional intake are the causes of anemia in adolescent girls